2023
DOI: 10.3390/plants12142680
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Metabolome, Transcriptome, and Physiology Revealed the Molecular and Physiological Response of Citrus sinensis Roots to Prolonged Nitrogen Deficiency

Abstract: Citrus sinensis seedlings were supplied with a nutrient solution containing 15 (control) or 0 (nitrogen (N) deficiency) mM N for 10 weeks. Extensive metabolic and gene reprogramming occurred in 0 mM N-treated roots (RN0) to cope with N deficiency, including: (a) enhancing the ability to keep phosphate homeostasis by elevating the abundances of metabolites containing phosphorus and the compartmentation of phosphate in plastids, and/or downregulating low-phosphate-inducible genes; (b) improving the ability to ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…In plants, the regulatory function of the m 6 A methylation component has been shown to be involved in various elements of RNA processing, such as RNA stability, alternative polyadenylation, and miRNA regulation. The authors also summarized the molecular mechanisms behind m 6 A modifications and recent insights into the diverse roles of m 6 A in RNA regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, the regulatory function of the m 6 A methylation component has been shown to be involved in various elements of RNA processing, such as RNA stability, alternative polyadenylation, and miRNA regulation. The authors also summarized the molecular mechanisms behind m 6 A modifications and recent insights into the diverse roles of m 6 A in RNA regulation.…”
mentioning
confidence: 99%
“…In the first, Cho et al [ 5 ] revealed correlations between ncRNAs and target coding RNAs through transcriptome analysis of suspension cells derived from damask rose petals, revealing important biological molecular mechanisms that occur during cell culture. In the second article, through an integrated analysis of the metabolome, transcriptome, and physiology, Lai et al [ 6 ] found that extensive metabolic and genetic reprogramming occurred in N-deficient roots, which not only improved the ability to detoxify reactive oxygen species and aldehydes, but also delayed root aging due to oxidative damage.…”
mentioning
confidence: 99%